Stroke rehabilitation using noninvasive cortical stimulation: aphasia. (August 2012) - Mylius, Veit; Zouari, Hela G; Ayache, Samar S; Farhat, Wassim H; Lefaucheur, Jean-Pascal
Poststroke aphasia results from the lesion of cortical areas involved in the motor production of speech (Broca's aphasia) or in the semantic aspects of language comprehension (Wernicke's aphasia). Such lesions produce an important reorganization of speech/language-specific brain networks due to an imbalance between cortical facilitation and inhibition. In fact, functional recovery is associated with changes in the excitability of the damaged neural structures and their connections. Two main mechanisms are involved in poststroke aphasia recovery: the recruitment of perilesional regions of the left hemisphere in case of small lesion and the acquisition of language processing ability in homotopic areas of the nondominant right hemisphere when left hemispheric language abilities are permanently lost. There is some evidence that noninvasive cortical stimulation, especially when combined with language therapy or other therapeutic approaches, can promote aphasia recovery. Cortical stimulation was mainly used to either increase perilesional excitability or reduce contralesional activity based on the concept of reciprocal inhibition and maladaptive plasticity. However, recent studies also showed some positive effects of the reinforcement of neural activities in the contralateral right hemisphere, based on the potential compensatory role of the nondominant hemisphere in stroke recovery.